At the gate of Christendom Jews, Muslims and "Pagans " in medieval Hungary, c. 1000 - c. 1300 - Berend, Nora (Cambridge studies in medieval life and thought, 2001)
Behandlar samexistens mellan kristna, judar, muslimer och kumener i Ungern under medeltiden.